Low carbon economic dispatch of integrated energy systems considering life cycle assessment and risk cost - Wu, Min (2023)
Integrated energy systems (IES) strengthen the interaction among electricity, gas and heat systems, and the concept of low-carbon development can further reduce the carbon emissions of IES. However, the uncertainty of IES reduces the supply flexibility and the complexity of different energy chains reduces the accuracy of carbon trading volume. Therefore, this study proposes a low carbon economic scheduling of IES considering life cycle assessment (LCA) and risk cost. First, the carbon emissions generated from different energy chain conversion processes in IES are analyzed by life cycle assessment method. Subsequently, the calculated carbon emission coefficients are introduced into the ladder-type carbon trading mechanism to further constrain the carbon emissions of IES. Specifically, the system risk is controlled using the conditional value-at-risk (CVaR) theory to obtain the day-ahead dispatch strategy. Finally, the effectiveness of the proposed method is verified based on the modified IEEE 39-node electric network, 20-node gas network and 6-node heat network models.